EMPOWERING FARMERS THROUGH SUBAK INSTITUTIONS TO SUSTAIN CULTURAL AND ECOTOURISM IN BALI - Ni Putu Nina Eka Lestari; Made Kembar Sri Budhi; Nyoman Windu Surya Sidantha (International Conference on Multidisciplinary Research Perspective, 2025)
This study explores the empowerment of farmers through the traditional Subak institution as a strategic model to sustain cultural and ecotourism in Bali. Subak, as a UNESCO-recognized cultural heritage, operates based on the Tri Hita Karana philosophy that harmonizes relationships among humans, nature, and the divine. Using a qualitative approach through observation, interviews, and focus group discussions in Subak Pulagan, Tampaksiring District, Gianyar Regency, this study identifies the social and economic functions of Subak that support both agricultural sustainability and tourism development. The findings reveal that Subak maintains traditional management practices emphasizing cooperation, trust, and community-based rituals that attract cultural tourists. Farmer empowerment occurs through targeted participation, group collaboration, and economic strengthening, including capital access and agritourism development. The study formulates a model of empowerment that integrates local wisdom, institutional participation, and socio-economic transformation, enabling Subak to function as a sustainable cultural and economic entity. This research contributes to the discourse on community-based tourism, sustainable agriculture, and cultural preservation, providing insights for policymakers and stakeholders in rural tourism development.